1999
DOI: 10.1089/hyb.1999.18.87
|View full text |Cite
|
Sign up to set email alerts
|

Possible Role of FDG-PET in the Early Prediction of Therapy Outcome in Liver Metastases of Colorectal Cancer

Abstract: Nonresectable colorectal cancer metastases in the liver respond to chemotherapy in 20-25% only. Early identification of nonresponders might allow the use of other regimens. In a limited feasibility study, it should be determined whether (a) a single high-dose chemotherapy application has an early effect on glucose-utilization, detectable and quantitatable by noninvasive positron emission tomography using [18F]-Fluoro-deoxyglucose (FDG-PET) and (b) assess its value as a predictor of the final therapeutic outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(15 citation statements)
references
References 9 publications
1
13
0
1
Order By: Relevance
“…In many studies, early metabolic changes measurable by [18normalF]FDG‐PET were highly predictive of clinical responses observed weeks to months later. Such findings have been reported for a variety of cancers, including lymphoma, as well as breast, esophageal, gastric, colorectal, head and neck, and non‐small‐cell lung cancers 5 , 16 . Early declines in [18normalF]FDG uptake generally correlate with longer progression‐free and overall survival.…”
Section: Introductionsupporting
confidence: 64%
“…In many studies, early metabolic changes measurable by [18normalF]FDG‐PET were highly predictive of clinical responses observed weeks to months later. Such findings have been reported for a variety of cancers, including lymphoma, as well as breast, esophageal, gastric, colorectal, head and neck, and non‐small‐cell lung cancers 5 , 16 . Early declines in [18normalF]FDG uptake generally correlate with longer progression‐free and overall survival.…”
Section: Introductionsupporting
confidence: 64%
“…Reference standards for the serial 18 F-FDG PET studies were the clinical response data, according to the World Health Organization (WHO) classification. In contrast to the studies of Findlay et al (10) and Bender et al (11), that study investigated absolute standardized uptake values (SUVs) and kinetic parameters and not fractional changes between baseline and follow-up scans. Even the quantitative values from the first PET study (at baseline) were predictive with respect to therapy outcome.…”
Section: Chemotherapy Response Monitoring In Advanced Colorectal Cancermentioning
confidence: 98%
“…Five studies (Table 1) reported the predictive value of 18 F-FDG PET in patients treated with chemotherapy for nonresectable colorectal cancer liver metastases (10)(11)(12)(13)(14). As early as 1996, Findlay et al (10) studied 18 patients before, at 1-2 wk after, and at 4-5 wk after 5-fluorouracil (5-FU) chemotherapy with or without interferon-a by using a nondedicated PET system with a limited resolution.…”
Section: Chemotherapy Response Monitoring In Advanced Colorectal Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…In these cases early identification of nonresponders might allow the use of other regimens (de Geus-Oei et al 2009;Bender et al 1999). 18F-FDG PET has emerged as a promising diagnostic modality, not only for staging and re-staging of colorectal cancer (Fig.…”
Section: Colorectal Cancermentioning
confidence: 99%